Calibration of Relative Humidity with Artificial Mass Method in Biogas Plant - Qoriatul Fitriyah; Muhammad Prihadi Eko Wahyudi; Markus Grömping (Politeknik Negeri Batam, 2021)
Biogas plant needs to be given specific amount of relative humidity setting in order to make it work optimally. It is one major factors of gas waste adsorption through final process of activated carbon in biogas plant, especially for hydrogen sulfide. Hydrogen sulfide is a side gas appeared in biogas plant which has to be removed by various processes, including the presence of activated carbon filter that usually appeared on last stage of biomass filtration process which is poisonous and corrosive to the metal parts. Today, air humidity gauges have been found quite a lot on the market. However, how accurate the device is, needs to be further proven in the laboratory, especially when the gauges have to face corrosive gases such as this H2S. Therefore, calibration for cheap and efficient relative humidity measurement is very necessary. The method will use comparison between RH reading and RH calculation based on parameters of plant settings in the form of gas composition mixture, flow duration, pressure, volumetric flow rate, and temperature. This paper will discuss how to calculate and measure calibration for relative humidity that is practical, simple and does not cost much so that it is expected to be used for low-funding research in biogas plant.